Pojęcie, formy i rola sieci w gospodarce przestrzennej - Miszczak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The main aim of this article is to show the rise of the role of networking horizontal connections, it means braid of economic, institutional, technological, and social relations in spatial economy. Network's analysis is believed to be a new instrument of regional dynamics' explanation. It has been agreed that the meaning of networking structures and interference in networking system have got stronger. It is believed that networking configurations will be dominant organizational economy's form in the near future. In the article, it was paid special attention to the fact of using networks as an instrument in innovations" development, especially in its interactive form. Different classifications of networks and networking milieus were also presented. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 236-250